Enlisting masculinity : the construction of gender in U.S. military recruiting advertising during the all-volunteer force - Brown, Melissa T., 1971- (New York ; Oxford : Oxford University Press, 2012)
Based on an analysis of more than 300 print advertisements as well as television commercials and recruiting websites, this book explores how the US military branches have deployed gender and, in particular, ideas about masculinity to sell military service to potential recruits during the all-volunteer force.
Includes bibliographical references and index.
Description based on print version details on publisher's website; title from home page (viewed on Mar. 13, 2012).
Keywords: Advertising -- Recruiting and enlistment -- Social aspects -- United States; Masculinity in advertising -- United States; United States -- Armed Forces -- Recruiting, enlistment, etc. -- History -- 20th century; United States -- Armed Forces -- Recruiting, enlistment, etc. -- History -- 21st century